Analisis Pengaruh Sanitasi dan Akses Air Bersih Terhadap Indeks Pembangunan Manusia di Jawa Tengah - Fita Purwaningsih; Suharno Suharno; Abdul Aziz Ahmad (Universitas Batanghari Jambi, 2021)
Human Development Index (HDI) of Central Java Province in 2015-2018 is the lowest compared to other provinces in Java Island. This study aims to analyze the effect of sanitation, water access, poverty, population, and economic growth on Human Development Index in Central Java Province at 2015-2018. The method used in this research is multiple linear regression with a panel data approach. The results show that sanitation, population, and economic growth have a positive and significant effect on the Human Development Index in Central Java Province. Poverty haa negative and significant effect on the Human Development Index in Central Java Province. Meanwhile, access to water has no effect on the Human Development Index in Central Java Province. This finding implies the need for equitable sanitation development for the population in Central Java Province. In addition, the government needs to increase economic growth and reduce the number of poor people.